Pengembangan Media Pembelajaran Biologi Berbasis HOTS melalui Platform Blog dengan Model PLOMP untuk Meningkatkan Motivasi dan Hasil Belajar - Nofamataro Zebua (GEN BIONIX: Jurnal Ilmiah Pendidikan Biologi, 2024)
This research aims to develop Higher Order Thinking Skills (HOTS)-based Biology learning media integrated with a blogplatform. The use of technology in education, especially in the context of the Industrial Revolution 4.0, demands innovation in teaching methods. This learning media is designed to support the development of critical thinking and problem solving skills inlearners through interactive and accessible content. This research uses the Research and Development (R&D) method with the PLOMP model, which involves the stages of initial investigation, prototype design, construction, evaluation, and implementation. Thetrial was conducted on 30 students of class XI at SMA Negeri 1 Telukdalam, with validation instruments, practicality test, and effectiveness test. The results of validation by experts showed that this media was very valid with a score of 94.7%, while the practicality test by teachers and students showed that this media was easy to use. The effectiveness of the media was measured through increased motivation and cognitive learning outcomes, as shown by an increase in post-test score from 57.2 to 87.7, with an N-gain of 0.71 (high category). The use of blogs as a learning platform proved effective in increasing motivation and understanding of biological concepts in students. This research makes a significant contribution to the development of learning media that is innovative and relevant to the demands of the Merdeka Curriculum and the needs of students in the digital era.